BNPd single-atom catalysts for selective hydrogenation of acetylene to ethylene: a density functional theory study - Wanqi Gong; Lihua Kang (Royal Society Open Science, 2018)
The mechanisms of selective hydrogenation of acetylene to ethylene on B11N12Pd single-atom catalyst were investigated through the density functional theory by using the 6-31++G** basis set. We studied the adsorption characteristics of H2 and C2H2, and simulated the reaction mechanism. We discovered that H2 underwent absolute dissociative chemisorption on single-atom Pd, forming the B11N12Pd(2H) dihydride complex, and then the hydrogenation reaction with C2H2 proceeded. The hydrogenation reaction of acetylene on the B11N12Pd complex complies with the Horiuti–Polanyi mechanism, and the energy barrier was as low as 26.55 kcal mol−1. Meanwhile, it also has a higher selectivity than many bimetallic alloy single-atom catalysts.